The Influence of Shade on the Growth and Production of Butterfly Pea Plants (Clitoria ternatea) - Asnur, Paranita; Kalsum, Ummu; Kanny, Putri Irene; Yuliani, Siska (International Journal on Food, Agriculture and Natural Resources, 2024)
Butterfly pea (Clitoria ternatea L.) is a medicinal plant known for its anthocyanin pigment content, which imparts a blue color to its flowers. This study aimed to evaluate the influence of shading on butterfly pea flower growth and production. The research design utilized a randomized complete block design (RCBD) for shading treatments. We replicated each treatment level four times, resulting in 20 experimental units, each containing four plants, for a total population of 80 plants. We conducted the experiment at the Experimental Garden of Gunadarma University Campus F7, implementing shade nets at different intensity levels (55%, 65%, 75%, and 85%), along with a control treatment without shading. We made observations on various plant growth parameters such as leaf count, plant length, days to first flower appearance, flower count, fresh weight, and dry weight. The results indicated that shading significantly influenced butterfly pea plants' growth. Plants without shading tended to exhibit better growth in several parameters, such as increased leaf count, higher plant length, and earlier days to first flower appearance. These findings underscore the importance of sunlight in supporting the growth and production of butterfly pea plants. Therefore, careful consideration of shade management is essential in agricultural practices to ensure optimal growth and maximum yield from butterfly pea plants.